Race, ethnicity and law - Deflem, Mathieu (Emerald Publishing Limited, 2017)
This new volume of Sociology of Crime, Law and Deviance addresses issues of race and ethnicity within the law and law-related phenomena. Even in today's so-called multicultural, post-racial world racial and ethnic concerns prevail in many aspects of modern law. Contributors to this volume examine racial and ethnic disparities in sentencing and punishment; the continued problematic nature of the African American experience within the US system; the criminalization of immigrants; racial inequities in the administration of drug laws; and the racial disparities that affect juvenile justice. This volume will be of interest to students and researchers in law, socio-legal studies, criminology, criminal justice, sociology and public policy.
Keywords: Discrimination in criminal justice administration -- United States.; Crime and race -- United States.; Racism in criminology -- United States.; Criminal justice, Administration of -- United States.; Race discrimination -- United States.; United States.; elektronické knihy; electronic books